Electrolyte solution, secondary battery, and electric device
By adding additives with amide bonds to the electrolyte and rationally preparing the electrolyte, the problem of corrosion of the steel shell of the cylindrical battery is solved, and the high-temperature storage performance and corrosion resistance of the battery are improved.
Patent Information
- Application Number
- CN202411812919.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The steel shell of cylindrical batteries is prone to corrosion, and the existing electrolyte design fails to effectively solve this problem, resulting in the possibility of corrosion and short circuit problems of the battery during long-term use.
Add additives with amide bonds to the electrolyte solution, and the corrosion reaction between HF and steel shell is suppressed by neutralizing the acidic components in the electrolyte solution. At the same time, the electrolyte is reasonably prepared to ensure that the content of cyclic carbonate, chain carbonate and unsaturated inorganic additives meets a specific range, so as to improve the high-temperature storage performance and corrosion resistance of the battery.
It effectively suppresses the corrosion problem of the steel shell of the cylindrical battery, improves the storage capacity and high-temperature storage performance of the battery, and avoids significant deterioration of the electrolyte impedance.
Smart Images

Figure CN119560633A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the field of batteries, and in particular, to electrolytes, secondary batteries and electrical devices. Background Art
[0002] In the field of new energy, electric vehicles have rapidly occupied the automobile market with their advantages of low energy consumption and zero carbon emissions, and are favored by the majority of users. With the increase in popularity, the problem of short driving range of electric vehicles has gradually been exposed, which requires lithium-ion batteries to further improve their energy density to meet the increasingly high driving range requirements. In order to improve the energy density of batteries, positive electrode materials are developing in the direction of high nickel ternary, negative electrode materials are developing in the direction of high silicon, and the structure of batteries is gradually transitioning from soft packs and square shells to cylindrical forms. In this field, the appearance of the known Tesla 4680 (battery diameter is 46 mm and height is 80 mm) large cylindrical battery has attracted the attention of the industry. It has higher energy density and safety, and is increasingly favored by other electric vehicle companies, which has led to various battery manufacturers competing to develop cylindrical batteries. The design and structure of cylindrical batteries are different from those of soft pack and square shell batteries. Due to the large pole winding tension and small internal space of cylindrical batteries, stainless steel materials are often used for their outer shells to meet sufficient pressure resistance. Compared with other materials (such as aluminum shells commonly used in square-shell battery cells), the corrosion resistance of stainless steel in cylindrical batteries is weaker. It is prone to both electrochemical corrosion (electrochemical oxidation) and chemical corrosion (such as acid corrosion). Since the steel shell is immersed in the electrolyte, the components of the electrolyte will pose a corrosion risk to the steel shell, which poses a higher challenge to the electrolyte.
[0003] However, for cylindrical batteries, the commonly used electrolyte design strategy in the industry is mainly focused on improving the electrolyte's wetting ability. There is generally no special solution for the corrosion problem of the steel shell, or the design strategy of high-voltage electrolyte is used to form a protective film on the surface of the steel shell through the film-forming passivation effect of specific additives, which can inhibit corrosion to a certain extent. However, this method is only a temporary solution and does not address the root cause. During long-term operation, the additives in the electrolyte are consumed and the protective effect on the steel shell is lost, and corrosion and short circuit problems will still occur. Summary of the invention
[0004] In view of the current steel shell corrosion problem of cylindrical batteries, the present invention proposes an additive and a corresponding electrolyte formula design. The additive proposed in the present invention can effectively neutralize the acidic components in the cylindrical battery electrolyte, thereby inhibiting the corrosion reaction between HF (acidic substances) and the steel shell and inhibiting the corrosion of the steel shell. In addition, through a reasonable formula design, the electrolyte proposed in the present invention can improve the high-temperature storage performance of the battery without significantly deteriorating the impedance.
[0005] The present application provides an electrolyte, which includes an additive having the following structural formula (I):
[0006]
[0007] Wherein, R1 and R2 are hydrogen or an alkyl group with 1 to 4 carbon atoms, and wherein, based on the total mass of the electrolyte, the mass fraction of the additive is 0.1% to 1%, optionally 0.3%. In the present application, an amide bond is present in the additive having the above structural formula (I), and the amide bond is alkaline, which can neutralize the acidic substance (HF) generated in the secondary battery, thereby inhibiting the reaction between HF and the cylindrical steel shell and inhibiting the corrosion problem of the secondary battery. Further, when 0.3% of the additive having the above structural formula (I) is added, the steel shell of the battery no longer has corrosion problems, and the storage capacity recovery of the battery is improved. In addition, when the amount of the additive having the above structural formula (I) is too low (for example, the mass fraction is less than 0.1%), the battery steel shell is significantly corroded, and when the amount of the additive having the above structural formula (I) is too large (for example, the mass fraction is higher than 1%), the internal resistance of the battery is significantly deteriorated.
[0008] In some embodiments, the additive is the following structure: In the present application, when the additive has this structure, the characteristics of the amide bond can be effectively exerted, thereby better neutralizing the acidic substances (HF) generated in the secondary battery.
[0009] In the present application, the electrolyte also includes cyclic carbonates, which include but are not limited to one or more of EC (ethylene carbonate), PC (propylene carbonate), FEC (fluoroethylene carbonate), etc., and based on the total mass of the electrolyte, the mass fraction of the cyclic carbonate is not less than 8% and not more than 24%.
[0010] In some embodiments, the cyclic carbonate includes fluoroethylene carbonate (FEC), and the mass fraction of the fluoroethylene carbonate is not higher than 8% and not lower than 2% based on the total mass of the electrolyte.
[0011] In some embodiments, the electrolyte further includes a linear carbonate, the linear carbonate includes DMC (dimethyl carbonate), and based on the total mass of the electrolyte, the mass fraction of DMC (dimethyl carbonate) is not less than 45%.
[0012] In some embodiments, the electrolyte further includes an unsaturated inorganic additive, which is an additive containing an unsaturated bond and an inorganic atom as the central atom, and wherein, based on the total mass of the electrolyte, the mass fraction of the unsaturated inorganic additive is not less than 0.3% and not more than 0.8%. In some embodiments, the unsaturated inorganic additive includes one or more of triphenyl phosphate (TPP), 1-propylene-1,3-sultone (PST) and tetravinylsilane (TVS). In the present application, when the unsaturated inorganic additive is too little (for example, the mass fraction is less than 0.3%), the positive electrode film formation is insufficient, and the high temperature storage performance of the secondary battery is deteriorated, and when the unsaturated inorganic additive is excessive (for example, the mass fraction is higher than 0.8%), the initial DCR of the secondary battery will increase dramatically, therefore, it is necessary to limit the mass fraction of the unsaturated inorganic additive to not less than 0.3% and not more than 0.8%.
[0013] Other embodiments of the present application provide a secondary battery, comprising: a positive electrode, comprising a positive electrode active material; a negative electrode, comprising a negative electrode active material; and an electrolyte, wherein the electrolyte is the above-mentioned electrolyte, wherein the positive electrode active material comprises lithium nickel cobalt manganese oxide, and based on the total mass of the positive electrode active material, the mass fraction of the nickel is not less than 80%, the negative electrode active material comprises silicon oxygen material or silicon carbon material, and based on the total mass of the negative electrode active material, the mass fraction of the silicon compound is not higher than 5%, and the upper limit of the operating voltage of the secondary battery is not less than 4.15V.
[0014] In some embodiments, the secondary battery is a cylindrical lithium-ion battery, and the diameter of the cylindrical lithium-ion battery is not less than 46 mm.
[0015] Still other embodiments of the present application provide an electrical device including the secondary battery described above.
[0016] In summary, the additive (I) proposed in the present invention has an amide bond in its structure, and the amide bond is alkaline and can neutralize the acidic substance (HF) generated in the secondary battery, thereby inhibiting the reaction between HF and the cylindrical steel shell and inhibiting the corrosion problem. Through reasonable formula design, the electrolyte proposed in the present invention can be well matched with the high-nickel positive electrode, effectively solving the problem of poor storage performance of the high-nickel cylindrical system, and solving the problem of steel shell corrosion. DETAILED DESCRIPTION
[0017] In the development of secondary batteries such as cylindrical batteries in the field of new energy, there is a problem of steel shell corrosion. Based on this, the present application adds additives to the electrolyte to neutralize the acidic substances (HF) generated in the secondary battery, thereby inhibiting the reaction between HF and the cylindrical steel shell and inhibiting the corrosion problem.
[0018] The present application provides an electrolyte, which includes an additive having the following structural formula (I):
[0019]
[0020] Wherein, R1 and R2 are hydrogen or an alkyl group with 1 to 4 carbon atoms, and wherein, based on the total mass of the electrolyte, the mass fraction of the additive is 0.1% to 1%, optionally 0.3%. In the present application, an amide bond is present in the additive having the above structural formula (I), and the amide bond is alkaline, which can neutralize the acidic substance (HF) generated in the secondary battery, thereby inhibiting the reaction between HF and the cylindrical steel shell and inhibiting the corrosion problem. Further, when 0.3% of the additive having the above structural formula (I) is added, the steel shell of the battery no longer has corrosion problems, and the storage capacity recovery of the battery is improved. In addition, when the amount of the additive having the above structural formula (I) is too low (for example, the mass fraction is less than 0.1%), the battery steel shell is significantly corroded, and when the amount of the additive having the above structural formula (I) is too large (for example, the mass fraction is higher than 1%), the internal resistance of the battery is significantly deteriorated.
[0021] In some embodiments, the additive is the following structure: In the present application, when the additive has this structure, the characteristics of the amide bond can be effectively exerted, thereby better neutralizing the acidic substances (HF) generated in the secondary battery.
[0022] In the present application, the electrolyte further includes cyclic carbonate, which includes but is not limited to one or more of EC (ethylene carbonate), PC (propylene carbonate), FEC (fluoroethylene carbonate), etc., and based on the total mass of the electrolyte, the mass fraction of the cyclic carbonate is not less than 8% and not more than 24%. In the present application, the content of the cyclic carbonate has an important influence on the initial DCR (impedance) of the secondary battery (has an important influence on wettability), and the mass fraction of the cyclic carbonate is too low (for example, the mass is less than 8%), which will lead to low conductivity and large DCR, while the mass fraction of the cyclic carbonate is too high (for example, the mass fraction is greater than 24%), which will lead to excessive viscosity of the electrolyte, and also increase the DCR.
[0023] In some embodiments, the cyclic carbonate includes fluoroethylene carbonate (FEC), and the mass fraction of fluoroethylene carbonate is not higher than 8% and not lower than 2% based on the total mass of the electrolyte. In the present application, if the mass fraction of FEC is too low (for example, lower than 2%), an effective SEI film (solid electrolyte interface film) cannot be formed on the surface of the silicon compound of the negative electrode, which will cause the storage capacity of the secondary battery to drop; and if the mass fraction of FEC is too high (for example, higher than 8%), the initial DCR of the secondary battery will be deteriorated, and the storage performance of the secondary battery will be deteriorated.
[0024] In some embodiments, the electrolyte further includes a linear carbonate, and the linear carbonate includes one or more of EMC (ethyl methyl carbonate), DMC (dimethyl carbonate), DEC (diethyl carbonate), etc. In the present application, the linear carbonate includes DMC (dimethyl carbonate), and based on the total mass of the electrolyte, the mass fraction of DMC (dimethyl carbonate) is not less than 45%, because DMC (dimethyl carbonate) plays an important role in reducing the DCR of the secondary battery, and a too low mass fraction of DMC (dimethyl carbonate) (i.e., less than 45%) will cause the DCR of the battery to increase, therefore, it is necessary to limit the mass fraction of DMC (dimethyl carbonate) to not less than 45%.
[0025] In some embodiments, the electrolyte further includes an unsaturated inorganic additive, which is an additive containing an unsaturated bond and an inorganic atom as the central atom, and wherein, based on the total mass of the electrolyte, the mass fraction of the unsaturated inorganic additive is not less than 0.3% and not more than 0.8%. In some embodiments, the unsaturated inorganic additive includes one or more of triphenyl phosphate (TPP), 1-propylene-1,3-sultone (PST) and tetravinylsilane (TVS). In the present application, when the unsaturated inorganic additive is too little (for example, the mass fraction is less than 0.3%), the positive electrode film formation is insufficient, and the high temperature storage performance of the secondary battery is deteriorated, and when the unsaturated inorganic additive is excessive (for example, the mass fraction is higher than 0.8%), the initial DCR of the secondary battery will increase dramatically, therefore, it is necessary to limit the mass fraction of the unsaturated inorganic additive to not less than 0.3% and not more than 0.8%.
[0026] Some other embodiments of the present application provide a secondary battery, which includes: a positive electrode, including a positive electrode active material; a negative electrode, including a negative electrode active material; and an electrolyte, wherein the positive electrode active material includes lithium nickel cobalt manganese oxide (for example, LiNi 0.9 Co 0.05 Mn 0.05 O2), and based on the total mass of the positive electrode active material, the mass fraction of nickel is not less than 80%, the negative electrode active material includes a silicon-oxygen material or a silicon-carbon material, and based on the total mass of the negative electrode active material, the mass fraction of the silicon compound is not higher than 5%, and the upper limit of the operating voltage of the secondary battery is not less than 4.15 V. In some embodiments, the secondary battery is a cylindrical lithium-ion battery, and the diameter of the cylindrical lithium-ion battery is not less than 46 mm.
[0027] Some other embodiments of the present application provide an electrical device including the above-mentioned secondary battery. In the present application, the secondary battery includes a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte. The relevant preparation method of the secondary battery is as follows.
[0028] (1) Preparation of positive electrode
[0029] The positive electrode active material is ternary NMC (LiNi 0.9 Co 0.05 Mn 0.05 O2), polyvinylidene fluoride as a binder and Super P (conductive carbon black) as a conductive agent are mixed in a weight ratio of 97-99:0.5-1.5:0.5-1.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the system becomes uniform and transparent to obtain a positive electrode slurry, and the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then the aluminum foil is dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode (pole sheet).
[0030] (2) Preparation of negative electrode
[0031] 96%-98% by mass of artificial graphite, 2%-4% by mass of SiC (silicon carbide) as negative electrode active materials, Super P as a conductive agent, sodium carboxymethyl cellulose (CMC-Na) as a thickener, and styrene-butadiene rubber (SBR) as a binder are mixed in a mass ratio of 94-98:0.5-1.5:0.5-1.5:1-3, deionized water is added, and a negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and then the copper foil is dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a negative electrode (pole sheet).
[0032] (3) Preparation of electrolyte:
[0033] In an argon atmosphere glove box with a water content of <10ppm, battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are mixed in proportions of 1%-11%, 1%-11%, 2%-8%, 6%-10%, and 45% or more of the total mass of the total electrolyte to form an organic solvent. Then, LiPF6, TPP, PST, TVS, and additives are added in proportions of 14%, 0.1%-0.2%, 0.1%-0.4%, 0.1%-0.2%, and 0.1%-1% of the total mass of the electrolyte, and mixed evenly to obtain an electrolyte. In the present application, the contents of all components are mass percentages calculated based on the total mass of the electrolyte. In addition, in the present application, the additive has the following structural formula (I):
[0034]
[0035] Wherein, R1 and R2 are hydrogen or an alkyl group having 1 to 4 carbon atoms.
[0036] (4) Preparation of isolation membrane:
[0037] Polypropylene film is used as the isolation film.
[0038] (5) Preparation of secondary batteries:
[0039] A 12 μm thick polypropylene film (PP) was used as a separator. The positive electrode, separator, and negative electrode prepared above were wound into a core in sequence, so that the separator was placed between the positive and negative electrodes to play a role of isolation. Then, the core was loaded into a large cylindrical battery shell of size 4695 (battery diameter was 46 mm, height was 95 mm), and the electrolyte prepared above was injected at 1.7 g / Ah, and then sealed, and the electrolyte was formed, and finally a cylindrical lithium-ion battery (i.e., lithium-ion battery) was prepared.
[0040] Those skilled in the art will understand that the above-described method for preparing a secondary battery is only an example, and other commonly used methods in the art may be used without departing from the contents disclosed in the present application.
[0041] The reagents and raw materials used in the present invention are commercially available.
[0042] The secondary battery can be applied to any suitable electrical device, including but not limited to electric vehicles.
[0043] Some specific embodiments and comparative examples are listed below to better illustrate the present application.
[0044] Example 1
[0045] (1) Preparation of positive electrode:
[0046] The positive electrode active material ternary NMC (LiNi 0.9 Co 0.05 Mn 0.05 O2), polyvinylidene fluoride as a binder and Super P as a conductive agent are mixed in a weight ratio of 98:1:1, N-methylpyrrolidone (NMP) is added, and the system is stirred under the action of a vacuum mixer until it becomes uniform and transparent to obtain a positive electrode slurry, and the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then the aluminum foil is dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain the positive electrode (pole sheet).
[0047] (2) Preparation of negative electrode:
[0048] 97% by mass of artificial graphite, 3% by mass of SiC as negative electrode active materials, Super P as a conductive agent, sodium carboxymethyl cellulose (CMC-Na) as a thickener, and styrene-butadiene rubber (SBR) as a binder are mixed in a mass ratio of 96:1:1:2, and deionized water is added. The negative electrode slurry is obtained under the action of a vacuum mixer, and the negative electrode slurry is evenly coated on the negative electrode current collector copper foil. After that, the copper foil is dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain the negative electrode (pole sheet).
[0049] (3) Preparation of electrolyte:
[0050] In an argon atmosphere glove box with a water content of <10ppm, battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are mixed in a ratio of 8%, 8%, 6%, 8%, and 55.3% of the total mass of the total electrolyte to form an organic solvent. Then, LiPF6, TPP, PST, TVS, and additives are added in a ratio of 14%, 0.1%, 0.2%, 0.1%, and 0.3% of the total mass fraction of the electrolyte, and mixed evenly to obtain an electrolyte (i.e., Example 1 in Table 1 below). In this Example 1, the additive has the following structural formula:
[0051] (4) Preparation of isolation membrane:
[0052] Polypropylene film is used as the isolation film.
[0053] (5) Preparation of secondary batteries:
[0054] A 12 μm thick polypropylene film (PP) was used as a separator. The positive electrode, separator, and negative electrode prepared above were wound into a core in sequence, so that the separator was placed between the positive and negative electrodes to play a role of isolation. Then, the core was loaded into a large cylindrical battery shell of size 4695, and the electrolyte prepared above was injected at 1.7 g / Ah, and then sealed, and the electrolyte was formed to finally prepare a cylindrical lithium-ion battery (i.e., lithium-ion battery).
[0055] Example 2
[0056] The preparation method is consistent with that in Example 1, except that in Example 2, the mass fractions of battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are 1%, 1%, 6%, 22%, and 55.3%, respectively.
[0057] Example 3
[0058] The preparation method is consistent with that in Example 1, except that in Example 3, the mass fractions of battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are 9%, 9%, 6%, 6%, and 55.3%, respectively.
[0059] Example 4
[0060] The preparation method is consistent with that in Example 1, except that in Example 4, the mass fractions of battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are 11%, 11%, 2%, 6%, and 55.3%, respectively.
[0061] Example 5
[0062] The preparation method is consistent with that in Example 1, except that in Example 5, the mass fractions of battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are 7%, 7%, 8%, 8%, and 55.3%, respectively.
[0063] Example 6
[0064] The preparation method is consistent with that in Example 1, except that in Example 6, the mass fractions of battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are 8%, 8%, 6%, 18.3%, and 45%, respectively.
[0065] Example 7
[0066] The preparation method is consistent with that of Example 1, except that in Example 7, the mass fractions of LiPF6, TPP, PST, TVS and additives are 14.1%, 0.1%, 0.1%, 0.1% and 0.3%, respectively.
[0067] Example 8
[0068] The preparation method is consistent with that of Example 1, except that in Example 8, the mass fractions of LiPF6, TPP, PST, TVS and additives are 9.1%, 0.2%, 0.4%, 0.2% and 0.3%, respectively.
[0069] Example 9
[0070] The preparation method is consistent with that of Example 1, except that in Example 9, the mass fractions of LiPF6, TPP, PST, TVS and additives are 14.2%, 0.1%, 0.2%, 0.1% and 0.1%, respectively.
[0071] Example 10
[0072] The preparation method is consistent with that of Example 1, except that the mass fractions of LiPF6, TPP, PST, TVS and additives in Example 10 are 13.3%, 0.1%, 0.2%, 0.1% and 1%, respectively.
[0073] Embodiment 11
[0074] The preparation method is consistent with that of Example 1, except that the additive in Example 11 has the following structural formula:
[0075] Example 12
[0076] The preparation method is consistent with that of Example 1, except that the additive in Example 3 has the following structural formula:
[0077] Example 13
[0078] The preparation method is consistent with that of Example 1, except that the additive in Example 3 has the following structural formula:
[0079] Comparative Example 1
[0080] The preparation method is consistent with that in Example 1, except that the mass fractions of battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in Example 1 are 2%, 2%, 2%, 24%, and 55.3%, respectively.
[0081] Comparative Example 2
[0082] The preparation method is consistent with that in Example 1, except that in Example 2, the mass fractions of battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are 10%, 10%, 8%, 2%, and 55.3%, respectively.
[0083] Comparative Example 3
[0084] The preparation method is consistent with that in Example 1, except that in Example 3, the mass fractions of battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are 10%, 10%, 0%, 10%, and 55.3%, respectively.
[0085] Comparative Example 4
[0086] The preparation method is consistent with that in Example 1, except that in Example 4, the mass fractions of battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are 5%, 5%, 10%, 10%, and 55.3%, respectively.
[0087] Comparative Example 5
[0088] The preparation method is consistent with that in Example 1, except that in Example 5, the mass fractions of battery-grade ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are 8%, 8%, 6%, 28.3%, and 35%, respectively.
[0089] Comparative Example 6
[0090] The preparation method is consistent with that in Example 1, except that the mass fractions of LiPF6, TPP, PST, TVS and additives in Example 6 are 14.2%, 0.1%, 0%, 0.1% and 0.3%, respectively.
[0091] Comparative Example 7
[0092] The preparation method is consistent with that in Example 1, except that the mass fractions of LiPF6, TPP, PST, TVS and additives in Example 7 are 13.4%, 0.3%, 0.4%, 0.3% and 0.3%, respectively.
[0093] Comparative Example 8
[0094] The preparation method is consistent with that in Example 1, except that the mass fractions of LiPF6, TPP, PST, TVS and additives in Example 8 are 14.3%, 0.1%, 0.2%, 0.1% and 0%, respectively.
[0095] Comparative Example 9
[0096] The preparation method is consistent with that in Example 1, except that the mass fractions of LiPF6, TPP, PST, TVS and additives in Example 9 are 13.1%, 0.1%, 0.2%, 0.1% and 1.2%, respectively.
[0097] The secondary batteries in the above-mentioned Examples 1-13 and Comparative Examples 1-9 can be tested by the following method:
[0098] (1) Normal temperature DC resistance DCR test
[0099] The secondary batteries in the above-mentioned embodiments 1 to 13 and comparative examples 1 to 9 were left standing at room temperature for 2 h, charged at a constant current of 1C to 50% SOC, i.e., 4.25V, then charged at a constant voltage of 4.25V to 0.05C cutoff, left standing for 30 min, and then discharged at a constant current of 0.33C to 2.5V; the 0.33C charge and discharge cycle was repeated twice, and the last discharge capacity was recorded as C0; after standing for 30 min, the battery cell was discharged at 0.33C to 50% C0, the SOC of the battery cell was adjusted to 50%, left standing for 30 min, the static terminal voltage V1 was recorded, the C0 constant current was discharged for 30 s, the terminal voltage V2 and the current I were recorded, and DCR=(V1-V2) / I was calculated.
[0100] (2) Secondary battery high temperature storage performance test
[0101] The battery cells were subjected to a storage test in a thermostat at a specified temperature (60°C). First, the initial capacity of the battery was tested at a current of 0.33C at room temperature (25°C). The secondary batteries obtained in Examples 1-13 and Comparative Examples 1-9 were fully charged and stored in a thermostat at 60°C for 15 days. The secondary batteries were then taken out and the recovery capacity of the batteries was tested at a current of 0.33C. The secondary batteries were then fully charged and stored. This process was repeated for 120 days, and the ratio of the recovery capacity on the 120th day to the initial capacity was collected and recorded as the storage capacity recovery rate.
[0102] (3) Steel shell corrosion test
[0103] The secondary batteries in Examples 1-13 and Comparative Examples 1-9 that were stored at high temperature (60° C.) for 120 days were disassembled, and the corrosion conditions of the inner wall of the steel shell were recorded.
[0104] The test results are shown in Table 1 below.
[0105] Table 1. Secondary battery performance test results of Examples 1 to 13 and Comparative Examples 1 to 9
[0106]
[0107]
[0108]
[0109] It can be seen from the above examples 1-13 that the electrolyte includes an additive having the following structural formula (I):
[0110]
[0111] Wherein, R1 and R2 are hydrogen or an alkyl group with 1 to 4 carbon atoms, and wherein, based on the total mass of the electrolyte, the mass fraction of the additive is 0.1% to 1%, optionally 0.3%, and the additive having the above structural formula (I) has an amide bond, which is alkaline and can neutralize the acidic substance (HF) generated in the secondary battery, thereby inhibiting the reaction between HF and the cylindrical steel shell and inhibiting the corrosion problem. Further, from the comparison of Examples 1, 9 and 10 and Comparative Examples 8-9, it can be seen that when 0.3% of the additive having the above structural formula (I) is added, the steel shell of the battery no longer has corrosion problems, and the storage capacity recovery of the battery is improved. In addition, it can be seen from Comparative Examples 8-9 that when the amount of the additive having the above structural formula (I) is too low (for example, the mass fraction is less than 0.1%, such as 0% in Comparative Example 8), the battery steel shell is significantly corroded, and when the amount of the additive having the above structural formula (I) is too large (for example, the mass fraction is higher than 1%, such as 1.2% in Comparative Example 9), the internal resistance of the battery is significantly deteriorated.
[0112] In addition, it can be seen from Examples 1, 11-13 that the additive is the following structure:
[0113] When the amide bond is used, the characteristics of the amide bond can be effectively utilized to better neutralize the acidic substances (HF) generated in the secondary battery.
[0114] From the comparison of Examples 1-3 and Comparative Examples 1-2, it can be seen that the content of cyclic carbonate EC (ethylene carbonate), PC (propylene carbonate), and FEC (fluoroethylene carbonate) has an important influence on the initial DCR (impedance) of the secondary battery (has an important influence on wettability). Too low a mass fraction of the cyclic carbonate (for example, less than 8% by mass, such as 6% in Comparative Example 1) will result in low conductivity and large DCR, while too high a mass fraction of the cyclic carbonate (for example, greater than 24% by mass, such as 28% in Comparative Example 2) will result in excessive viscosity of the electrolyte, which also increases the DCR. Therefore, the mass fraction of the cyclic carbonate needs to be limited to not less than 8% and not more than 24%.
[0115] From the comparison of Examples 1, 4-5 and Comparative Examples 3-4, it can be seen that the mass fraction of FEC has an important influence on the performance of the secondary battery. If the mass fraction of FEC is too low (for example, less than 2%, such as 0% in Comparative Example 3), an effective SEI film (solid electrolyte interface film) cannot be formed on the surface of the silicon compound of the negative electrode, which will cause the storage capacity of the secondary battery to drop; while the mass fraction of FEC is too high (for example, higher than 8%, such as 10% in Comparative Example 4), the initial DCR of the secondary battery will be deteriorated, and the storage performance of the secondary battery will be deteriorated. Therefore, the mass fraction of fluoroethylene carbonate needs to be no higher than 8% and no lower than 2%.
[0116] From the comparison of Examples 1, 6 and Comparative Example 5, it can be seen that the chain carbonic acid in the electrolyte includes DMC (dimethyl carbonate), and based on the total mass of the electrolyte, the mass fraction of DMC (dimethyl carbonate) is not less than 45%. This is because DMC (dimethyl carbonate) plays an important role in reducing the DCR of the secondary battery. A too low mass fraction of DMC (dimethyl carbonate) (i.e., less than 45%, such as 35% in Comparative Example 5) will lead to an increase in the DCR of the battery. Therefore, it is necessary to limit the mass fraction of DMC (dimethyl carbonate) to not less than 45%.
[0117] From the comparison of Examples 1, 7-8 and Comparative Examples 6-7, it can be seen that the unsaturated inorganic additives in the electrolyte play an important role, and the unsaturated inorganic additives include triphenyl phosphate (TPP), 1-propylene-1,3-sultone (PST) and tetravinylsilane (TVS). Based on the total mass of the electrolyte, the mass fraction of the unsaturated inorganic additive is not less than 0.3% and not more than 0.8%. When the unsaturated inorganic additive is too little (for example, the mass fraction is less than 0.3%, such as 0.2% in Comparative Example 6), the positive electrode film formation is insufficient and the high temperature storage performance of the secondary battery is deteriorated. When the unsaturated inorganic additive is excessive (for example, the mass fraction is higher than 0.8%, such as 1% in Comparative Example 7), the initial DCR of the secondary battery will increase dramatically. Therefore, it is necessary to limit the mass fraction of the unsaturated inorganic additive to not less than 0.3% and not more than 0.8%.
[0118] The features of several embodiments are summarized above so that those skilled in the art can better understand aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for implementing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that this equivalent construction does not deviate from the spirit and scope of the present invention, and that they can make multiple changes, substitutions and changes herein without departing from the spirit and scope of the present invention.
Claims
1. An electrolyte, characterized in that: Including additives having the following structural formula (I): Wherein, R1 and R2 are hydrogen or an alkyl group with 1 to 4 carbon atoms, and wherein, based on the total mass of the electrolyte, the mass fraction of the additive is 0.1% to 1%.
2. The electrolyte according to claim 1, characterized in that The additive has the following structure:
3. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the mass fraction of the additive is 0.3%.
4. The electrolyte according to claim 1, characterized in that The electrolyte further comprises cyclic carbonate, wherein the mass fraction of the cyclic carbonate is not less than 8% and not more than 24% based on the total mass of the electrolyte.
5. The electrolyte according to claim 4, characterized in that The cyclic carbonate includes fluoroethylene carbonate. Based on the total mass of the electrolyte, the mass fraction of the fluoroethylene carbonate is not higher than 8% and not lower than 2%.
6. The electrolyte according to claim 5, characterized in that The electrolyte further includes a chain carbonate, and the chain carbonate includes dimethyl carbonate, wherein the mass fraction of the dimethyl carbonate is not less than 45% based on the total mass of the electrolyte.
7. The electrolyte according to claim 1, characterized in that It also includes an unsaturated inorganic additive, wherein the unsaturated inorganic additive contains an unsaturated bond and has an inorganic atom as the central atom, and wherein, based on the total mass of the electrolyte, the mass fraction of the unsaturated inorganic additive is not less than 0.3% and not more than 0.8%.
8. The electrolyte according to claim 7, characterized in that The unsaturated inorganic additive includes one or more of triphenyl phosphate, 1-propylene-1,3-sultone and tetravinylsilane.
9. A secondary battery, characterized in that: include: A positive electrode, including a positive electrode active material; A negative electrode, including a negative electrode active material; as well as An electrolyte, wherein the electrolyte is the electrolyte according to any one of claims 1 to 8, Wherein, the positive electrode active material comprises lithium nickel cobalt manganese oxide, and based on the total mass of the positive electrode active material, the mass fraction of the nickel is not less than 80%, The negative electrode active material comprises a silicon-oxygen material or a silicon-carbon material, and based on the total mass of the negative electrode active material, the mass fraction of the silicon compound is not higher than 5%, and The upper limit of the working voltage of the secondary battery is not less than 4.15V.
10. The secondary battery according to claim 9, characterized in that: The secondary battery is a cylindrical lithium-ion battery, and the diameter of the cylindrical lithium-ion battery is not less than 46 mm.
11. An electrical device, characterized in that: The invention comprises the secondary battery according to any one of claims 9 to 10.
Citation Information
Patent Citations
Electrolyte solution, electrochemical device, and electronic device
CN114207903A
Organic carbonate additives for nonaqueous electrolyte in alkali metal electrochemical cells
EP0803924A2
Side-chain functionalized polynorbornenes as ionomers and as membrane materials for alkaline electrolysis of water, and fuel cell
WO2024245731A1